2004
DOI: 10.1097/01.jcp.0000125684.82219.53
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Response to Antipsychotics of Schizophrenia Patients Treated in Routine Clinical Practice

Abstract: In routine practice, subjective response to antipsychotics is becoming a critical outcome measure among schizophrenia patients. This study sought to compare subjective response to atypical (risperidone and olanzapine) and typical antipsychotic drugs. Using a naturalistic cross-sectional design, we examined subjective response to antipsychotics (satisfaction with medication and subjective tolerability), psychopathology, side effects, emotional distress, and awareness in schizophrenia patients stabilized on atyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 50 publications
2
19
1
Order By: Relevance
“…Previous reports from Western or African countries have revealed that subjective responses to medication were associated with side effects [29,31,32], psychopathology [18,29,[31][32][33], and employment status [29][30][31], but were independent of other sociodemographic variables or length of illness [18,[30][31][32][33][34]. In this study, however, age and gender (China) and length of illness (Japan), were significantly associated with DAI-30, but employment status showed no significant association.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Previous reports from Western or African countries have revealed that subjective responses to medication were associated with side effects [29,31,32], psychopathology [18,29,[31][32][33], and employment status [29][30][31], but were independent of other sociodemographic variables or length of illness [18,[30][31][32][33][34]. In this study, however, age and gender (China) and length of illness (Japan), were significantly associated with DAI-30, but employment status showed no significant association.…”
Section: Discussioncontrasting
confidence: 55%
“…Polypharmacy of antipsychotics and concurrent use of anticholinergics, anxiolytics, or hypnotics were more frequently found in Tokyo. Past studies [4,5,18,19] indicated that patients' subjective responses are generally more favorable to atypical antipsychotics than to typical antipsychotics, but in Tokyo, the advantage of atypical antipsychotics would be compromised by frequent concomitant use of typical antipsychotics. The differences between the two countries align with past reports d Patients' subjective evaluation using a 4-point Likert scale from 1(not bothered at all) to 4 (bothered very much) *P \ 0.05, **P \ 0.01, ***P \ 0.001 Table 4 Stepwise multiple regression analysis of DAI- comparing prescription practices for inpatients [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…39 In brief, the study is a longitudinal naturalistic investigation with open comparison of parallel groups of schizophrenia patients stabilized on atypical (risperidone or olanzapine) and typical antipsychotic agents, who were then followed for 1 year. Patients were recruited via the case register, and treatment had been initiated before recruitment to the study, according to clinical indications as determined by the treating physician.…”
Section: Methodsmentioning
confidence: 99%
“…In our first report from this crosssectional analysis, we found that atypical drugs were superior to typical antipsychotics in measures of both satisfaction with medication and subjective tolerability. 39 The present report compares QOL outcomes of treatment with risperidone or olanzapine with typical antipsychotic agents across demographic, illness-related, and treatmentrelated factors. Particularly, we sought to (a) compare general and domain-specific QOL outcomes of schizophrenia patients receiving atypical (risperidone or olanzapine) and typical antipsychotic agents; (b) examine between-group differences in the QOL outcomes across demographic and illness-related variables, daily doses and duration of treatment, side effects, subjective tolerability, and concomitant drugs; and (c) evaluate correlation between self-report and observer-rated QOL instruments.…”
mentioning
confidence: 99%
“…Several studies have shown that atypical drugs such as clozapine and olanzapine, are conducive to reducing smoking, reduce the desire to smoke and, finally, relieve the withdrawal symptoms [10,66,67]. Also, in patients taking atypicals, a lower level of distress is observed [68]. In this study, distress turned out to be a significant predictor of smoking, therefore it is possible that this mechanism is important in explaining the observed difference.…”
Section: Discussionmentioning
confidence: 52%